Additive layer manufacturing of poly (ether ether ketone) via FDM. (15th July 2018) - Rinaldi, Marianna; Ghidini, Tommaso; Cecchini, Federico; Brandao, Ana; Nanni, Francesca
Abstract: The present paper concerns the additive layer manufacturing of polyether-ether–ketone (PEEK) by means of fused deposition modelling (FDM). PEEK is a high-performance polymer (outstanding mechanical properties, high thermal stability and chemical resistance), suitable for space applications, that, however, due to its semicrystalline nature is difficult to process; moreover, only very few FDM printers suitable for PEEK are currently available on the market. In this paper the results of mechanical (tensile tests), thermal (DSC), microstructural (XRD) and morphological (OM and CT-scans) testing of FDM printed PEEK samples are reported, and some of them compared with that of the extruded filament prior to printing. The results evidence the effect of the process on the printed parts in terms of thermal and mechanical properties including fracture mechanism. Moreover, the impact of printing parameters (as infill and filament deposition pattern) on the final mechanical performance is evidenced too, as it is linked to the resisting cross section. Graphical abstract: Highlights: 3D printed PEEK shows no change in terms of thermal and microstructural properties. The failure mechanism depends on the printing direction. CT-scan Defect analysis shows the discrepancy between CAD and 3D printed parts. The infill influence on mechanical property is not directly correlated. Percentage of porosity in 3D printed sample is not dependent on printing direction.